Italian Food? Sounds Good! Made in Italy and Italian Sounding Effects on Food Products' Assessment by Consumers - Bonaiuto, Flavia; De Dominicis, Stefano; Ganucci Cancellieri, Uberta; Crano, William D.; Ma, Jianhong; Bonaiuto, Marino (Frontiers in Psychology, 2021)
Italian sounding – i.e., the Italian appearance of a product or service brand irrespective of its country of origin – represent a global market phenomenon affecting a wide range of economic sectors, particularly the agro-food sector. Although its economic impact has been repeatedly stressed from different point of views (policy, economy, culture, etc.), systematic scientific knowledge regarding its social-psychological bases is lacking. Three studies carried out in three different countries (Italy, China and USA) address this literature gap. Different consumers groups (both native and/or non-native) are targeted regarding major product categories pre-selected being the major Italian food goods within the specific country according to piloting (oil and/or pasta). In each study, the main independent variable (product version) has been manipulated by presenting real products images (previously pre-selected within the tested food category in each country market), whose Italianness degree is effectively manipulated in the main study variable (product version) across three or four levels (Protected Designation of Origin Made in Italy; Made in Italy; Italian Sounding; Generic Foreign). Main hypotheses are tested via a survey with the specific product images administered to samples in Italy (N = 204, 148 Italians and 56 non-Italians), in China (N = 191, 100 Chinese and 91 non-Italian expatriates in China), in the USA (N = 237 US citizens). Across the three studies, results show that Made in Italy products, compared to the other ones, are advantaged in terms of the main dependent variables: reputation profile, general reputation, attitude and willingness to pay (WTP). Moreover, Italian Sounding products are endowed with corresponding significant advantages when compared to the Generic Foreign by non-Italian samples. Results details reveal the specific social-psychological profile of the Italian Sounding products in terms of either weaknesses or strengths when compared to both the Made in Italy products and the Generic Foreign ones, differentially in the eyes of Italian and non-Italian consumers across different countries. Finally, consistently across the three studies, the extent to which a food product is perceived to be Italian affects consumers’ willingness to pay for that product is mediated by the product’s reputation.